Investigation of microstructure and tribological performances of high-fraction TiC/graphene reinforced self-lubricating Al matrix composites. (January 2023) - Lin, Fei; Ren, Mengyuan; Wu, Hui; Jia, Fanghui; Lu, Yao; Huo, Mingshuai; Yang, Ming; Chen, Zhixin; Jiang, Zhengyi
Abstract: Al-10.0 vol% (TiC and GNPs) composites were fabricated with different volume ratios of TiC and GNPs from 10.0:0.0–8.0:2.0 by powder metallurgy. The results show particle free zones (PFZs) in as-sintered composites decrease and distributions of reinforcements become more uniform, and the hardness and wear resistance of hybrid composite increase as TiC-to-GNPs ratio decreases. Al-8.5 vol% TiC-1.5 vol% GNPs has the highest hardness at 200.5 HV and the best wear resistance with a wear rate of 4.99 × 10 −4 mm 3 /Nm based on the collaborative effects of TiC and GNPs, respectively. However, as the GNPs fraction increases to 2.0 vol%, the hardness and wear resistance of the composite drop drastically because of GNPs agglomeration.